Effects of the COVID-19 crisis on household food consumption and child nutrition in Mozambique - Margherita Squarcina; Eva-Maria Egger (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This study investigates the short-term impacts of an aggregate socioeconomic shock on household food consumption and children's nutrition using the case of the COVID-19 pandemic in Mozambique. In response to the economic downturn, households are expected to adjust their food choices both in terms of quality, towards cheaper and unhealthier food, and quantity, reducing diet diversification and increasing the exposure to malnutrition, mainly for children. Empirical evidence on such immediate effects is still scarce, mainly due to a lack of data. This paper aims to fill the evidence gap by relying on household survey data from 2019-20, which includes a detailed consumption module and anthropometric measures for children under five. We use a repeated cross-sectional econometric analysis to look at the variation in household food consumption and child nutrition before and after the pandemic. The results show that there has been a significant reduction in household food consumption and per capita caloric intake and an increase in stunting, especially among newborn children.
Keywords: C21; D12; O12; 330; COVID-19; food consumption; nutrition; Mozambique